The Power of Integrating Bite-Sized Learning and Teacher Talk on Telegram Amid Pandemic - Febrianingrum, Lasmi; Rabbianty, Eva Nikmatul (OKARA: Jurnal Bahasa dan Sastra, 2022)
Bite-sized learning works in synergy with microlearning. It promotes small activities and content to understand the materials in a sequence of ways with meaningful information. Telegram, one social media, can be used as an online learning platform. Bite-sized learning encourages Telegram features in providing simple and fun activities comprehensively. Teachers shared knowledge and skills, organized teaching activities, and helped students practice through teacher talks, either in organizing a classroom or achieving the teaching goals. Since this study explored how bite-sized learning and teacher talk on Telegram in L2 Listening class, this study used a qualitative approach with a case study. The result revealed how well the teacher communicates with the students during online learning in giving instruction, sharing ideas and knowledge, stimulating students to respond to the teacher and material, cultivating students’ intellectual ability, and managing classroom activities. Furthermore, those activities need to be more noticed, extra patience and energy, a more creative in delivering instruction and materials to initiate and stimulate students to respond and engage in the class. These study results imply that during online learning, the teacher talk and bite-sized learning need to be implemented and improved well and creatively to promote students’ understanding, interaction and engagement.